Inovasi Pemasaran Kreatif melalui Penggunaan Komik Sebagai Sarana Edukasi Marketing untuk Meningkatkan Penjualan - Marcella Fanyssa Agata; Agatha Carmelline Tyasratri Evangelina; Akhmad Bagus Nuryanto (Adi Karsa: Jurnal Teknologi Komunikasi Pendidikan, 2026)
In an increasingly competitive business world, marketing is key to the survival and development of a business, both in global and local markets. Amidst this competition, many SMEs, such as food stalls, still use traditional and ineffective marketing strategies. Incorrect marketing strategies can result in significant sales declines and even bankruptcy for most SMEs. This necessitates educational programs designed to educate SMEs, especially food stall owners, to understand the importance of innovation in marketing strategies and adapt to technological developments and market needs. Therefore, engaging, easy-to-understand, and relevant learning media are needed to ensure marketing education is accessible to a wide range of audiences. Therefore, this study aims to develop and test the effectiveness of comics as a creative and interactive marketing education tool. The research method used is Research and Development (R&D) with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observation, interviews, expert validation, and pre- and post-tests given to two groups of respondents: group A (using comics) and group B (without comics). The results of the effectiveness test showed that group A experienced a 59.6% increase in understanding and a 77.8% increase in turnover, while group B only experienced a 22.6% increase in understanding and a 16.1% increase in turnover. Based on these results, it can be concluded that the comic media "Want to Make Your Shop More Popular, BUT HOW?!" is effective as a marketing education medium that can significantly increase the understanding of marketing concepts, sales results, and business profits.